Evaluasi Sistem Manajemen Keuangan Pada Peternakan Skala Kecil Untuk Meningkatkan Profitabilitas - Sutarto, Sutarto; Erubun, Delvis (Jurnal Ilmu Peternakan Indonesia, 2024)
Effective financial management systems are key to improving the profitability of small-scale livestock enterprises. This study evaluated the financial management systems implemented in small-scale livestock enterprises and identified challenges and opportunities for improvement. The methods used included qualitative data analysis through interviews with farmers and direct observation of existing financial management practices. The results showed that many farmers still rely on conventional financial management practices, resulting in a lack of efficiency and transparency in financial management. The application of information technology, such as the Point of Sales (PoS) system, is proven to improve operational efficiency and simplify the recording of financial transactions. In addition, financial management training for farmers improved their understanding of the importance of good financial management. The study also found that production cost and human resource management factors had a significant effect on business profitability. Therefore, a holistic approach that includes cost analysis, marketing and human resource management is necessary to achieve optimal results. The resulting recommendations include the implementation of an integrated financial management system, increased training for farmers, and support from the government and related institutions. It is expected that these measures can improve the profitability and sustainability of small-scale livestock enterprises.